(untitled) (Research, Society and Development, 2020)
The aim of this study was to present a systematic review and scientometric analysis on commercial eggs production in Brazil. For the systematic review, articles targeted to the described subtopics were selected. In contrast, the scientometric analysis was performed considering the articles indexed on CAPES, SCIELO, SCORPUS and WEB OF SCIENCE platforms. Subsequently, the articles found were analyzed and grouped according to the number of publications per year, the theme addressed in the publications, regions where the publications occurred, main authors, list of journals where the articles were published and the qualifications of the journals. The results showed that articles on commercial eggs have decreased in recent years, with Salmonella detection and contamination being the most addressed topic (30%). In addition, it was possible to observe that publications are more concentrated in the Southeast (35%) and Northeast (15%). The author with the most publications on the subject was Pinto, A. T., being the journal Arquivo Brasileiro de Medicina Veterinária and Zootecnia being the one that published the most on the subject (20%). Finally, all articles found were published in a journal with expressive qualities greater than B3, with A2 being the one that most covered the publications, totaling 40%, demonstrating the importance of the theme. Furthermore, it is concluded that there are regions where research on commercial eggs production is still not widespread. In addition, this study presents a current overview of the production of commercial eggs in Brazil, providing possibilities for expanding knowledge through studies in areas and topics little researched.